Functioning of the Energy Sector Under Crisis Conditions—A Polish Perspective - Joanna Florek; Ryszard Staniszewski; Dorota Czerwińska-Kayzer; Dariusz Kayzer (Energies)
In the context of the coronavirus pandemic and the armed conflict between Russia and Ukraine, energy security is essential to economic challenges nowadays. The basis for the proper operating of the energy sector is to ensure a stable supply of energy to end users and to secure finances of energy companies, so that they can operate sustainably in times of uncertainty. In our studies, we have addressed this issue with the main objective of assessing the state of energy security from the perspective of the stability of the financial situation of energy sector companies in the context of the global energy crisis and a sustainable energy future. Financial indicators and a canonical variable analysis were used to examine the financial situation of companies in the energy sector and to describe links between selected groups of energy companies. Such companies operating during political and economic instability did not record worse financial results than in the year 2018. It was found that in case-studied firms, total debt decreased and moreover, liquidity and return on assets improved. Companies have focused on securing their financial health and ensuring the stability of their energy supplies and the issue of the environmental impact of energy production has unfortunately become a secondary concern. Nevertheless, in the event of further crises, it is reasonable to assume that a focus on maintaining liquidity and generating profits for energy companies will be more important to companies than environmental challenges and the fight against climate change.